Processos de subjetivação e percursos de sentiduralização na discursividade literária em Lygia Fagundes Telles - Rosa, Ismael Ferreira (2013)
This research aims at analyzing the literary discursivity at Lygia Fagundes Telles, observing its linguistic, historical and subjective tridimensionalities, especially that related to the production of senses and subjects in the woman field from three novels: Ciranda de Pedra (1954), Verão no Aquário (1963) e As Horas Nuas (1989). Based on Discourse Analysis, particularly on studies of Pêcheux about sense and subject, and based on dialogical-polyphonic discussions on language, literature and subject of the Bakhtin Circle conjugated to Foucault s understanding about literary universe and its discursive practices, as well as notions like literary discourse and paratopos of Maingueneau and the becoming notion by Deleuze and Guattari, besides Barthes and Blanchot s discussions, we intend to expose a reader-look at identity processes and subjectmental and sensemental (de)constructions of this following analytical cut: Virgínia, Raíza e Rosa Ambrósio. We propose a theoretical-analytical of interpretive nature research from which cuts of novels linguistic materiality serve as a starting point to approach the way how the literary discursivity moves and produces subjects and senses. Thus, based on Santos and Ferreira-Rosa, we built the analytical and methodological device nonessential in triple-helix, through which we associated analytical centers, in accordance with the cut technique proposed by Orlandi and with recurrence and regularity criteria, establishing combinations of constituted, constituent and constitutive elements. Instituting three helix, a subjectmental one, a sensemental one and an aesthetical one, whose rotating and contrarotating movements represent the tridimensionality of the literary discursivity operation in its sensementalization, we searched to describe and to analyze the construction process of those cut subjects. A process that revealed the establishment of an enunciative subjectmental instance woman characterized by the decentering, the identity fragmentation. An establishment signaled by sensemental courses that depart from a hard side, pass by the fluid and reach the liberty in a way non-linearly and non-continuously. In fact, courses marked by dialogues, silences, acts and actions-forces that build senses of submission, confutation, contradiction and coercion.